Modern approaches to the prevention of venous thromboembolic complications in patients with active cancer - Yu. A. Fedotkina; E. P. Panchenko («REMEDIUM GROUP» Ltd., 2023)
Cancer is one of the most significant risk factors for venous thromboembolic complications (VTEC), which combines deep vein thrombosis and pulmonary embolism. Of the many well-known risk factors for VTEC, only cancer is associated with a 4-fold increased risk of venous thrombosis, and in cancer patients receiving chemotherapy the risk increases by up to 6.5-fold. Venous thrombosis is increasingly common in cancer patients and contributes significantly to the course of the underlying disease and mortality, especially when combined with additional risk factors, the most significant of which are surgery and chemotherapy treatment. The prevention and treatment of VTEC in cancer patients is a challenge, primarily due to the pathogenesis of cancer-associated thrombosis, the presence of additional risk factors associated with cancer, the high risk of haemorrhagic complications, reduced renal function and the recurrent nature of VTEC. Aspects of safe prevention remain an integral part of the management of patients with active cancer. The most vulnerable periods for the development of VTEC are the periods when the patient is hospitalised for surgical or therapeutic treatment and the long period of chemotherapy treatment on an outpatient basis. A comprehensive approach to the prevention of VTEC in patients with cancer should primarily involve careful selection of high-risk patients at each stage of treatment of the malignancy; these patients are the ones who will benefit most from drug thromboprophylaxis. The treatment of an already confirmed VTEC in a cancer patient always involves the additional challenges of drug interactions and increased haemorrhagic risk due to prolonged use of treatment doses of anticoagulants, which may in turn affect the effectiveness of chemotherapy or the efficiency and safety of anticoagulant therapy.